The Impact of Football Initiatives on the Formation of a Culture of Health among the Younger Generation - Tsybanyuk, O.; Dariichuk, S.; Tymchuk, Liudmyla; Комісарик, Марія (My University, 2025)
The aim of the study was to assess the effectiveness of football-based sports projects in fostering a healthy lifestyle among children. An experimental sports project was tested to evaluate its influence on the formation of health-oriented behaviors. The study involved 111 boys aged 9–10 from general secondary schools in Kyiv, divided into an experimental group (n=59) and a control group (n=52). Participants were selected with parental consent. The experimental group followed a healthy lifestyle program; the control group did not. Questionnaires were used as the primary method for monitoring the experimental impact. The results of the formative experiment demonstrated the effectiveness of implementing football programs in shaping a healthy lifestyle in children. Positive dynamics were particularly evident in the emotional-motivational and activity-related components, while changes in the cognitive component were less pronounced. Overall, there was a significant increase in the number of children showing medium to high levels of healthy lifestyle indicators (p<0.05). The findings provided a basis for optimizing the school educational process through the integration of health-preserving technologies.
Keywords: Football; Sports Programs; Healthy Lifestyle; Health; Children